The Invisible Flood: The Chemistry, Ecology, and Social Implications of Coastal Saltwater Intrusion. (1st May 2019) - Tully, Kate; Gedan, Keryn; Epanchin-Niell, Rebecca; Strong, Aaron; Bernhardt, Emily S; BenDor, Todd; Mitchell, Molly; Kominoski, John; Jordan, Thomas E; Neubauer, Scott C; Weston, Nathaniel B
Abstract: Saltwater intrusion is the leading edge of sea-level rise, preceding tidal inundation, but leaving its salty signature far inland. With climate change, saltwater is shifting landward into regions that previously have not experienced or adapted to salinity, leading to novel transitions in biogeochemistry, ecology, and human land uses. We explore these changes and their implications for climate adaptation in coastal ecosystems. Biogeochemical changes, including increases in ionic strength, sulfidation, and alkalinization, have cascading ecological consequences such as upland forest retreat, conversion of freshwater wetlands, nutrient mobilization, and declines in agricultural productivity. We explore the trade-offs among land management decisions in response to these changes and how public policy should shape socioecological transitions in the coastal zone. Understanding transitions resulting from saltwater intrusion—and how to manage them—is vital for promoting coastal resilience.